Implementasi Program Digital Detox dalam Meningkatkan Konsentrasi Hafalan Al-Quran Santri - Asiana; Rohmadi; Dodi Irawan (PAI RAFAH, 2025)
This study aims to: (1) How is the Implementation of the Digital Detox. Program in Improving the Concentration of Memorizing the Al-Quran of Students at the Al Fikri Tahfidz House in Palembang. (2) What are the Supporting and Inhibiting Factors of the Digital Detox Program in Improving the Concentration of Memorizing the Al-Quran of Students at the Al Fikri Tahfidz House in Palembang. This study is a type of descriptive research using a qualitative approach. The data obtained using interviews, observations, and documentation. The validity test in this study is triangulation of sources, and techniques. The data analysis techniques used in this study are data reduction, data presentation, and drawing conclusions. The results of the study showed that: (1) The implementation of the Digital Detox program at Rumah Tahfidz Al Fikri Palembang was successfully implemented through socialization, supervision, and provision of supporting replacement activities. (2) The main supporting factors for the success of this program are family support, supervision of ustadz/ustadzah, and varied replacement activities.